Platelet and Haemostasis are the Main Targets in Severe Cases of COVID-19 Infection; a System Bioinformatics Study - Mona Zamanian Azodi; Babak Arjmand; Mohammadreza Razzaghi; Mostafa Rezaei Tavirani; Alireza Ahmadzadeh; Mohammad Rostaminejad (Archives of Academic Emergency Medicine, 2021)
Introduction: Many proteomics-based and bioinformatics-based efforts are made to detect the molecular mechanism of COVID-19 infection. Identification of the main protein targets and pathways of severe cases of COVID-19 infection is the aim of this study.